2020
DOI: 10.21037/apm.2019.09.15
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and infection outcomes of bacterial colonization in patients with indwelling abdominal drains for malignant ascites

Abstract: Background: Indwelling abdominal drains for intermittent drainage is an effective treatment for refractory malignant ascites, bacterial colonization and subsequent drain-related infection is however a common concern. This study aimed to investigate the patterns of bacterial colonization and the subsequent infection outcomes in patients with indwelling abdominal drains. Methods: All consecutive advanced cancer patients with newly inserted indwelling abdominal drains and who were under the service of the ascites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
0
11
2
Order By: Relevance
“…Third, the incidence of peritonitis in the LTAD and LVP groups were 6% and 11%, respectively, despite the LVP group being on antibiotic prophylaxis. This is in contrast to a recent study that had shown a 21% frequency of infection 2 . A possible reason for such a difference may be that only 18% of patients belonged to Child Class C which itself is a risk factor for, and predisposes to, the development of infections.…”
contrasting
confidence: 86%
“…Third, the incidence of peritonitis in the LTAD and LVP groups were 6% and 11%, respectively, despite the LVP group being on antibiotic prophylaxis. This is in contrast to a recent study that had shown a 21% frequency of infection 2 . A possible reason for such a difference may be that only 18% of patients belonged to Child Class C which itself is a risk factor for, and predisposes to, the development of infections.…”
contrasting
confidence: 86%
“…Our study cannot be compared to that of Chan et al 4 as overall, <20% of their cohort had cirrhosis. More importantly, they used non‐tunneled drains, which are associated with a higher infection risk than tunnelled drains (peritonitis 4.4% vs 21%) 5 .…”
contrasting
confidence: 63%
“…It is also inconsistent with the evidence reported following the use of a central venous catheter for malignant ascites drainage: 0-2.3% peridrain infection and absence of peritonitis/sepsis complications (3,4). It is even more important to notice the high frequency of infection reported in the study conducted by Chan et al (2), because all patients underwent ascites drainage in a specialized clinic, under the supervision of a medical professional. Other study reported a significantly lower frequency of infections in patients performing drainage unassisted at home (4).…”
mentioning
confidence: 78%
“…In particular, peritonitis may be fatal. A study conducted by Chan et al (2) adds valuable evidence on this matter. They performed a retrospective study investigating the patterns of bacterial colonization and the subsequent infection outcomes in patients using indwelling abdominal drains for intermittent drainage of malignant ascites.…”
mentioning
confidence: 97%